Building policy coherence into Nigeria’s agri-food system: options for more effective coordination and integration - Osei-Amponsah, Charity; Appiah, Sarah; Nicol, Alan; Balana, Bedru (International Water Management Institute, 2024)
Nigeria faces a plethora of challenges ranging from malnutrition and food insecurity, violent land tenurial conflicts and water insecurity in a changing climate. This situation threatens economic growth and development, particularly, the achievement of key targets of the Sustainable Development Goals related to SDG 1 (eliminate all forms of poverty), SDG 2 (zero hunger), SDG 5 (gender equality), SDG 6 (Clean water and sanitation), SDG 13 (climate action), SDG 14 (Conserve and sustainably use the oceans, seas, and marine resources for sustainable development) and 15 (life on land). Another pertinent challenge impeding the achievement of the goals is the lack of synergies and inadequate coordination between and within policies and development programming. The CGIAR Initiative on National Policies and Strategies (NPS), aims to contribute to agri-foods system transformation, by identifying ways of building stronger food, land and water policies with greater coherence and investment capacity, to support Nigeria in addressing current crises and future development needs. This guidance brief is based on insights from a study on the policy (in)coherence in food, land and water systems in Nigeria. Using the CGIAR NPS, Policies and Institutions Landscape Framework, four policies: the National Water Resources Policy 2016; Agriculture Promotion Policy 2016; The National Policy on Food Safety and its Implementation Strategy (2014) and the National Biodiversity Strategy and Action Plan 2016-2020, were analysed. The study indicates that most of the FLW policies significantly complement one another (horizontal coherence), by promoting food sufficiency and improved livelihoods for especially rural dwellers. However, the National Water Resources Policy 2016, Agriculture Promotion Policy (2016) and the National Biodiversity Strategy and Action Plan (2016-2020) have contradicting objectives. There is seemingly harmonious coordination (vertical coherence) of the formulated policies across different tiers of government in the country, but not evident through the implementation of the policies, due to less coordination and accountability. All the four selected policies analyzed in the study were found to be financially incoherent. The average annual national financial commitment fails to meet up with the annual investment requirements of the FLW systems, leading to policy ineffectiveness in addressing critical socio-economic and agri-food challenges. The Initiative can support policy makers in addressing the incoherences and positively transform FLW systems by co-creating and facilitating policy frameworks and pathways.